Removal of photoredox catalysts from polymers synthesized by organocatalyzed atom transfer radical polymerization. Issue 19 (14th July 2022) - Chism, Katherine A.; Corbin, Daniel A.; Miyake, Garret M.
Abstract: Organocatalyzed atom transfer radical polymerization (O‐ATRP) is a method of producing polymers with precise structures under mild conditions using organic photoredox catalysts (PCs). Due to the unknown toxicity of PCs and their propensity to introduce color in polymers synthesized by this method, removal of the PC from the polymer product can be important for certain applications of polymers produced using O‐ATRP. Current purification methods largely rely on precipitation to remove the PC from the polymer, but a more effective and efficient purification method is needed. In this work, an alternative purification method relying on oxidation of the PC to PC · + followed by filtration through a plug to remove PC · + from the polymer and removal of the volatiles was developed. A range of chemical oxidants and stationary phases were tested for their ability to remove PCs from polymers, revealing chemical oxidation by N ‐bromosuccinimide followed by a filtration through a silica plug can remove up to 99% of the PC from poly(methyl methacrylate). Characterization of the polymer before and after purification demonstrated that polymer molecular weight, dispersity, and chain‐end fidelity are not signficantly impacted by this purification method. Finally, this purification method was tested on a range of dihydrophenazine, phenoxazine, dihydroacridines, and phenothiazine PCs, revealing the strength of the chemical oxidant must match the oxidation potential of the PC for effective purification. Abstract :